MODEL INTEGRASI PENDIDIKAN KARAKTER KESELAMATAN BERLALU LINTAS PADA EKSTRAKURIKULER PKS TINGKAT SMA/SMK: MODEL INTEGRASI PENDIDIKAN KARAKTER KESELAMATAN BERLALU LINTAS PADA EKSTRAKURIKULER PKS TINGKAT SMA/SMK - Hidayati, Tri Susila; Ayu, Brasie Pradana Sela Bunga Riska; Hadi, Suprapto; Siswanto, Joko (Universitas Negeri Surabaya, 2023)
High school/vocational school students are in a transitional phase towards greater independence and responsibility, so it is important to have a strong traffic safety character. The school security patrol extracurricular in high schools/vocational schools has an important role in shaping the traffic safety character of students. The integration of traffic safety character education with school security patrol extracurriculars in high schools/vocational schools is proposed with an integration model. Modeling refers to a character education management scheme with 18 indicators in 6 schools in 4 regions with data collection using surveys and questionnaires. The resulting traffic safety character is included in the category that is still not good. The proposed integration model applies the design of the assisted school with adjustments to raw input, transformation, instrumental input, environmental input and output. The integration model is carried out by making collaborative actions between stakeholders to achieve excellent traffic safety characteristics at the high school/vocational school level.